Peningkatan Teknologi Produksi dan Strategi Pemasaran Produk Kosmetik di Perusahaan Belukar Organics - Alla Asmara; I Wayan Budiastra; Deva Primadia; Fiona Hanberia Innayah; Titis Priyowidodo; Elizabeth Sonya Lumbantoruan; Tarisa Fadillah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Belukar organics is a newly developed business entity for the production of liquid body soap and body scrubs. The volume of production and sales of liquid body soap and scrubs is still limited, around 360 bottles and 24 kilograms per year due to lack of marketing strategy and ineffective production process. Therefore, the objectives of program held for 7 months is to increase the production and sales volumes of liquid soap and body scrub. The program activities focused on training and supervision on production technology, packaging, management, marketing and facilitation of production and packaging equipment. In the production aspect, the new lay out of production process was set up, the new production technology and the SOPs were applied. In the management aspect, training and supervision in the Business Model Canvas, Business Plan and Action Plan, bookkeeping and accounting were carried out. In the marketing aspect, training and marketing supervision were carried out covering aspects of branding, promotion and digital marketing. With training and mentoring activities, the production of Belukar organics liquid soap increased from 39 bottles to 117 bottles per month. Body scrub production increased from 2 kg to 7 kg per month. Sales turnover of liquid body soap also increased from 4,3 million rupiah per month to 12,3 million rupiah per month, while body scrubs increased from 2 million rupiah to 6,5 million rupiah per month. PKM activities succeeded in increasing the volume of production and sales of liquid body soap and body scrub Belukar Organics by around 300%.